Involvement of women in Pantja goat rearing in Tarai region of Uttarakhand (Indian Journal of Animal Production and Management, 2016)
An extensive survey was carried out to explore the participation of women in Pantja goat rearing in Tarai  region of Uttarakhand. The results of study clearly showed that women played a predominant role in goat  rearing. A majority of women farmers performed assistance at the time of parturition (73.95%) followed by  cleaning of animal shed (61.40%), care of sick animal (56.43%), stall feeding after grazing (54.11%), care of  young stock (52.40 %), dusting (54.26%) and grazing of goats (47.44%). In the same tasks the involvement  of men was 26.05, 35.04, 42.02, 40.93, 45.89, 45.74 and 46.51 percent whereas, adolescent participated  in the above mentioned tasks to the extent of 00.0, 3.57, 1.55, 4.96, 1.71, 0.00 and 6.05 percent. The  results of the present study indicated that the women farmers were capable of managing the goats in a  similar fashion to men even without any formal training, and their skills could be strengthened by imparting  to them proper scientific training (related to goat production technology) suited to the ecosystem of Tarai region of Uttarakhand. It is quite obvious from the observations collected during the survey that there is an  urgent need for the policy makers to pay more attention to the involvement of women farmers involved in  goat production by enhancing their skills through education provided by the extension workers, voluntary  organizations and government agencies. It will not only increase the efficiency of goat production but also  elevate the socio economic conditions of the rural masses of the district.
Keywords: Cleaning; Feeding; Grazing; Goat rearin; Involvement